SOME BIOLOGICAL AND ECOLOGICAL CHARACTERISTICS OF Callerya speciosa (Champ.) Schot AS THE SCIENTIFIC BASIS FOR RARE AND VALUABLE MEDICINAL PLANT PRESERVATION - Thi Nu Hoang, Ta; Minh Quang, Nguyen (Journal of Forestry Science and Technology, 2018)
Callerya speciosa (Champ.) Schot is a valuable medicinal plant, used mainly in traditional medicine as a tonic, and for cough, fever, urinary retention treatment... In recent years, Callerya speciosa are being exploited massively resulting in decreasing gene sources. The study was carried out to study some morphological and ecological characteristics of Callerya speciosa in Hoanh Bo, Quang Ninh province and Son Dong, Bac Giang province. The research showed that Callerya speciosa was a species of erect shrub or climber - leaves irriparipinnate. Leaflets 3 - 11, irregularly ovoid, glabrous on both surfaces, margin entire, secondary nerves pinnate, apice acutes, base obtuses. The species is distributed mainly in rehabilitated forests, with an average elevation of 110 - 160 alt., tree component in forest conditions is reletively diverse; Shrubs and herbaceous carpet grow at average rate. At present, it is mainly exploited from nature and sold to collectors. In order to preserve and develop Callerya speciosa, apart from measures to prevent illegal devastative exploitation of natural resources, there should be measures to propagandize, raise awareness for officials, local people and visitors. In addition, it is necessary to study the creation of plant varieties, to promote the planting and promotion of natural regeneration in places where natural conditions are appropriate.